Effects of transplanted GDNF gene modified marrow stromal cells on focal cerebral ischemia in rats - Wang, Yunliang; Geng, Tongchao (Frontiers in Integrative Neuroscience, 2011)
Objective: To evaluate the therapeutic effect of transplanted Glial cell derived neurotrophic factor (GDNF) modified marrow stromal cells (MSCs) on an experimental ischemic brain injury based on the behavioral, morphological and immunohistochemical observations. Methods: The MSCs from newborn rats were cultured in vitro. The cerebral ischemia and reperfusion model was established in rats by using the suture method. 3 days after model establishment, the animals were injected with prepared MSCs via their caudal veins. The animals were then divided into a sham-operation group, ischemia group, MSCs transplantation group or GDNF+MSCs transplantation group and were scored for their neurobehavioral manifestations at 3, 14 and 28 days after the transplantation was performed. At this time, the survival condition of intracerebral transplanted cells was measured by laser confocal microscopy while the effect of transplantation on the GDBF expression in the ischemic brain tissue was evaluated. Results: The MSCs cells transfected with GDNF gene were characterized by green fluorescence. 3 days after the transplantation, the animals that underwent the cell transplantation showed significantly better behavioral data than the controls. 14 days after transplantation, the animals transplanted with GDNF gene modified MSCs were better than those transplanted with common MSCs. As compared with common MSCs transplantation, GDNF+MSCs transplantation was significantly more effective in reducing apoptotic cell volume and enhancing Bcl-2 expression, which was favorable for the ischemic brain injury. Conclusions: Transplanted GDNF modified MSCs can improve the nervous function and have a protective effect on the ischemic brain injury through reducing apoptotic cell volume and enhancing the expression of antiapoptotic gene Bcl-2.